Composite substrate, method for producing the same, and method for producing gallium oxide crystal film

JP7644812B2Active Publication Date: 2025-03-12NGK CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2023517095
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-04-27
Filing Date
2022-02-28
Publication Date
2025-03-12
Estimated Expiration
2042-02-28

AI Technical Summary

Benefits of technology

【0011】 本発明の複合基板及び複合基板の製法では、α-Ga2O3結晶膜と下地基板との間の剥離が抑制された複合基板を提供できる。こうした効果が得られる理由は、例えば、α-Ga2O3結晶膜中にアルカリ金属元素の少なくとも1種が好適な濃度で含まれているためと推察される。本発明の複合基板の製法は、α-Ga2O3結晶膜と下地基板との間の剥離が抑制された複合基板を製造するのに適している。また、本発明の酸化ガリウム結晶膜の製法では、α-Ga2O3結晶膜と下地基板との間の剥離が抑制されたクラックの少ない複合基板から下地基板を除去して自立したα-Ga2O3結晶膜を得るため、クラックの少ない酸化ガリウム結晶膜が得られる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007644812000003
    Figure 0007644812000003
  • Figure 0007644812000004
    Figure 0007644812000004
  • Figure 0007644812000005
    Figure 0007644812000005
Patent Text Reader

Abstract

A composite substrate 50 comprises a base substrate 52 and a α-Ga2O3 crystal film 54 provided on the base substrate 52. The α-Ga2O3 crystal film 54 has a film thickness of 10 μm or more, and has a content of at least one kind of alkali metal element of 1.2×1015 atoms / cm3 to 1.0×1018 atoms / cm3.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composite substrate, a method for producing the composite substrate, and a method for producing a gallium oxide crystal film. [Background technology]

[0002] In recent years, gallium oxide (Ga2O3) has been attracting attention as a semiconductor material. Gallium oxide is known to have five crystal forms, α, β, γ, δ, and ε. Among these, α-Ga2O3, which is a metastable phase, has a very large band gap of 5.3 eV and is expected to be used as a power semiconductor material. For example, Patent Document 1 discloses a semiconductor device having a base substrate with a corundum type crystal structure, a semiconductor layer with a corundum type crystal structure, and an insulating film with a corundum type crystal structure, and describes an example in which an α-Ga2O3 film is formed as a semiconductor layer on a sapphire substrate. Patent Document 2 discloses a semiconductor device having an n-type semiconductor layer mainly composed of a crystalline oxide semiconductor having a corundum structure, a p-type semiconductor layer mainly composed of an inorganic compound having a hexagonal crystal structure, and an electrode. In the examples of this patent document 2, it is disclosed that a diode is fabricated by forming an α-Ga2O3 film having a metastable corundum structure as an n-type semiconductor layer and an α-Rh2O3 film having a hexagonal crystal structure as a p-type semiconductor layer on a c-plane sapphire substrate. α-Ga2O3 is also expected to be applied to phosphors. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2014-72533 A [Patent Document 2] JP 2016-25256 A Summary of the Invention [Problem to be solved by the invention]

[0004] However, when attempting to thicken the α-Ga2O3 crystal film, peeling can occur between the α-Ga2O3 crystal film and the base substrate when the α-Ga2O3 crystal film is grown on the base substrate such as a sapphire substrate, resulting in frequent cracks at and around the peeled portion. For this reason, there has been a demand for a method to suppress the peeling between the α-Ga2O3 crystal film and the base substrate.

[0005] The present invention has been made to solve such problems, and a main object of the present invention is to suppress peeling between an α-Ga2O3 crystal film and an underlying substrate. [Means for solving the problem]

[0006] As a result of intensive research to solve the above-mentioned problems, the inventors came up with the idea of ​​immersing an α-Cr2O3 substrate as a base substrate in an aqueous solution containing Ga ions to create a supercritical state at a temperature of 390°C or higher and a pressure of 22.1 MPa or higher. They then found that with this method, an α-Ga2O3 crystal film is formed on the surface of the base substrate, and even if the α-Ga2O3 crystal film is thickened to 10 μm or more, peeling is unlikely to occur between the α-Ga2O3 crystal film and the base substrate. They also found that the α-Ga2O3 crystal film formed on the base substrate contains at least one alkali metal element within a predetermined range, and thus completed the present invention.

[0007] That is, the composite substrate of the present invention is A base substrate; A film having a thickness of 10 μm or more and a content of at least one alkali metal element of 1.2×10 15 atoms / cm 3 Above 1.0×10 18 atoms / cm 3 An α-Ga2O3 crystal film having the following structure: It is equipped with the following:

[0008] The method for producing a composite substrate of the present invention includes the steps of: A method for producing the above-mentioned composite substrate, comprising the steps of: The starting substrate is immersed in an aqueous solution containing Ga ions and placed in a supercritical state at a temperature of 390°C or higher and a pressure of 22.1 MPa or higher, thereby producing the α-Ga2O3 crystal film on the surface of the starting substrate.

[0009] The method for producing a gallium oxide crystal film of the present invention comprises the steps of: The base substrate is removed from the composite substrate to obtain the free-standing α-Ga2O3 crystal film. Note that the free-standing α-Ga2O3 crystal film refers to the composite substrate from which the base substrate has been removed, and may be transferred onto another substrate once the base substrate has been removed.

[0010] Alternatively, the method for producing a gallium oxide crystal film of the present invention includes the steps of: The base substrate is removed from the composite substrate produced by the above-mentioned composite substrate production method to obtain the self-supporting α-Ga2O3 crystal film. Effect of the Invention

[0011] The composite substrate and the manufacturing method of the composite substrate of the present invention can provide a composite substrate in which peeling between the α-Ga2O3 crystal film and the base substrate is suppressed. The reason for obtaining such an effect is presumably, for example, that at least one type of alkali metal element is contained in the α-Ga2O3 crystal film at a suitable concentration. The manufacturing method of the composite substrate of the present invention is suitable for manufacturing a composite substrate in which peeling between the α-Ga2O3 crystal film and the base substrate is suppressed. In addition, in the manufacturing method of the gallium oxide crystal film of the present invention, a free-standing α-Ga2O3 crystal film is obtained by removing the base substrate from a composite substrate in which peeling between the α-Ga2O3 crystal film and the base substrate is suppressed and peeling between the α-Ga2O3 crystal film and the base substrate is suppressed, so that a gallium oxide crystal film with few cracks is obtained. [Brief description of the drawings]

[0012] [Figure 1] FIG. [Diagram 2] FIG. [Diagram 3] FIG. 1 is a schematic diagram of a hydrothermal synthesis system 20. [Figure 4]4 is a SEM image of the surface of the composite substrate obtained in Example 1. [Diagram 5] 4 is a cross-sectional SEM image of the composite substrate obtained in Example 1. [Figure 6] FIG. 2 is a schematic cross-sectional view showing the configuration of the AD device 120. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] A preferred embodiment of the present invention will be described below with reference to the drawings. Fig. 1 is a cross-sectional view of a composite substrate 50, Fig. 2 is a vertical cross-sectional view of a pressure-resistant vessel 10, and Fig. 3 is a schematic diagram of a hydrothermal synthesis system 20.

[0014] [Composite board] The composite substrate 50 is a plate-shaped member, and includes a base substrate 52 and an α-Ga2O3 crystal film 54 provided on the base substrate 52. The area of ​​the composite substrate 50 is, for example, 1 mm 2 More than 10mm, preferably 2 That's all.

[0015] The base substrate 52 is a substrate that serves as a seed crystal of the α-Ga2O3 crystal film 54. The base substrate 52 is preferably a substrate having a corundum structure, and is particularly preferably a substrate (biaxially oriented substrate) oriented along two axes, the c-axis and an axis perpendicular to the c-axis (such as the a-axis or m-axis). The biaxially oriented substrate may be a polycrystal or a mosaic crystal (a collection of crystals with slightly misaligned crystal orientation), or may be a single crystal. The base substrate 52 may be c-axially oriented with an off angle of 10° or less in the substrate normal direction. The base substrate 52 may further include another substrate on the surface opposite to the surface (formation surface 52a) on which the α-Ga2O3 crystal film 54 is formed.

[0016] The base substrate 52 is an α-Cr2O3 substrate. The α-Cr2O3 substrate may be, for example, one made of α-Cr2O3 that does not contain components other than unavoidable impurities (called an α-Cr2O3 high-purity substrate), or one that contains α-Cr2O3 and metal elements other than Cr, such as Ti, Fe, Al, Mg, Si, and Ca, in a range where the total amount does not exceed the number of moles of Cr. These metal elements and / or metalloid elements may be solid-solved in α-Cr2O3, or may be solid-solved in α-Cr2O3 as a crystal phase such as an oxide crystal (for example, α-Al2O3). Such a solid solution is also called an α-Cr2O3 solid solution. As the α-Cr2O3 substrate, an α-Cr2O3 high-purity substrate and an α-Cr2O3 solid solution substrate containing at least one of Fe and Ti are particularly suitable.

[0017] The α-Ga2O3 crystal film 54 is formed on one surface (formation surface 52a) of the base substrate 52 with a thickness of 10 μm or more. The α-Ga2O3 crystals 55 constituting the α-Ga2O3 crystal film 54 are crystals having a corundum structure. The α-Ga2O3 crystal film 54 is preferably oriented along two axes, the c-axis and an axis perpendicular to the c-axis (biaxial orientation). The α-Ga2O3 crystal film 54 may be a polycrystal, a mosaic crystal, or a single crystal. The α-Ga2O3 crystal film 54 may be c-axis oriented with an off angle of 10° or less to the substrate normal direction. The α-Ga2O3 crystal film 54 contains at least one alkali metal element in an amount of 1.2×10 15 ~1.0×10 18 atoms / cm 3 The alkali metal elements include Li, Na, and K. The content of each of Li, Na, and K is 1.2×10 15 atoms / cm 3 Above 1.0×10 18 atoms / cm 3or less. The α-Ga2O3 crystalline film 54 may have a crystal orientation difference of 0.4° or less between the (0001) plane and the (10-10) plane of the base substrate 52. The α-Ga2O3 crystalline film 54 may have an X-ray rocking curve (XRC) half width of 2000 arcsec or less between the (006) plane and the (104) plane of the α-Ga2O3 crystalline film 54. The α-Ga2O3 crystalline film 54 may have a Cr and Ni content of 2.0×10 15 ~1.0×10 17 atoms / cm 3 The α-Ga2O3 crystal film 54 may have a Li, Na, and K content of 1.2×10 15 ~1.0×10 18 atoms / cm 3 The α-Ga2O3 crystal film 54 may contain a dopant. Examples of the dopant include Group 14 elements such as carbon (C), silicon (Si), germanium (Ge), tin (Sn), and lead (Pb). By making the α-Ga2O3 crystal film 54 contain a dopant, the conductivity of the α-Ga2O3 crystal film 54 can be controlled.

[0018] [Composite substrate manufacturing method] Next, a method for producing composite substrate 50 will be described. In the method for producing composite substrate 50, base substrate 52 is immersed in an aqueous solution containing Ga ions, and the solution is brought into a supercritical state at a temperature of 390°C or higher (preferably 400°C or higher) and a pressure of 22.1 MPa or higher, thereby forming α-Ga2O3 crystal film 54 on the surface of base substrate 52.

[0019] Examples of the aqueous solution containing Ga ions include an aqueous gallium halide solution, an aqueous gallium nitrate solution, an aqueous gallium sulfate solution, and an aqueous gallium hydroxide solution. Examples of the gallium halide solution include gallium chloride, gallium bromide, and gallium iodide. The aqueous solution containing Ga ions may contain an alkali metal element (alkali metal ion). Examples of the alkali metal element include Li, Na, and K. The aqueous solution containing Ga ions is adjusted to a pH of preferably 9.0 to 11.0 (more preferably 9.5 to 10.5) with a pH adjuster. As the pH adjuster, an aqueous solution of an alkali metal hydroxide (e.g., a KOH aqueous solution) or an aqueous solution containing ammonium ions (e.g., ammonium water) may be used. The Ga ion concentration of the aqueous solution containing Ga ions is not particularly limited, but may be, for example, 0.1 M or more and 10 M or less.

[0020] The base substrate 52 to be immersed in the aqueous solution containing Ga ions is preferably one in which a process-affected layer has been removed from at least one surface (the surface to be formed surface 52a) by CMP (chemical mechanical polishing), annealing, etching, RIE (reactive ion etching), or the like. When the base substrate 52 is immersed in the aqueous solution containing Ga ions, if the surface from which the process-affected layer has been removed is placed in contact with the aqueous solution containing Ga ions, an α-Ga2O3 crystal film 54 is formed on the surface from which the process-affected layer has been removed. When the base substrate 52 is immersed in the aqueous solution containing Ga ions, the base substrate 52 may be placed or fixed on a Pt jig or the like and immersed.

[0021] To bring the aqueous solution containing Ga ions into a supercritical state at a temperature of 390°C or more and a pressure of 22.1 MPa or more, it is preferable to put the aqueous solution containing Ga ions into a pressure vessel and set the temperature to 390°C or more and the pressure to 22.1 MPa or more. The pressure is determined by the internal volume of the pressure vessel, the amount of the aqueous solution put into the pressure vessel, the temperature in the pressure vessel, and the setting of the pressure control valve. The reaction time is not particularly limited, but may be, for example, 0.5 hours or more and 100 hours or less. After the reaction is completed, the temperature in the pressure vessel is lowered, and the base substrate 52 (composite substrate 50) with the α-Ga2O3 crystal film 54 attached thereto is taken out from the pressure vessel.

[0022] When it is desired to generate an α-Ga2O3 crystal film 54 containing a dopant, ions corresponding to the dopant may be added to the aqueous solution containing Ga ions. Examples of dopants include Group 14 elements such as carbon (C), silicon (Si), germanium (Ge), tin (Sn), and lead (Pb). By adding a dopant to the α-Ga2O3 crystal film 54, the conductivity of the α-Ga2O3 crystal film 54 can be controlled.

[0023] An example of a pressure vessel is shown in FIG. 2. The pressure vessel 10 in FIG. 2 is made of stainless steel, and a lid 12 with a male thread and a protrusion 12a is screwed into a female thread provided at the opening of a bottomed cylindrical vessel body 11. The internal volume of the pressure vessel 10 is preferably 50 mL or more. The vessel body 11 of the pressure vessel 10 contains an aqueous solution 14 containing Ga ions. This aqueous solution 14 is preferably adjusted to a pH of 9.0 to 11.0 (more preferably a pH of 9.5 to 10.5). A base substrate 52 arranged on the bottom surface of a box-shaped jig 16 made of Pt is immersed in this aqueous solution 14. The base substrate 52 is arranged so that the surface from which the processing-affected layer has been removed faces upward.

[0024] FIG. 3 is a schematic diagram of a hydrothermal synthesis system 20. In this hydrothermal synthesis system 20, a pressure vessel 10 is set in an electric furnace housing 22. A heater 24 and a thermocouple 26 for measuring the temperature inside the furnace are attached inside the electric furnace housing 22. A pressure vessel thermocouple 28 for measuring the internal temperature of the pressure vessel 10 is attached to the pressure vessel 10. The power supplied to the heater 24 is controlled so that the furnace temperature measured by the thermocouple 26 for measuring the temperature inside the furnace becomes the set temperature. A pipe 30 is connected to the pressure vessel 10. One end 30a of the pipe 30 is disposed inside the pressure vessel 10, and the other end 30b of the pipe 30 is disposed in the atmosphere. The pipe 30 is cooled by cooling water in a cooling water tank 40. A pressure gauge 32, a safety valve 34, and a pressure regulating valve 36 are attached to the pipe 30 between the cooling water tank 40 and the other end 30b. The entire pressure vessel 10 is heated by the heater 24 so that the internal temperature of the pressure vessel 10 is 390° C. or higher and the internal pressure of the pressure vessel 10 is 22.1 MPa or higher. The internal pressure of the pressure vessel 10 is determined by the internal volume of the pressure vessel 10, the amount of the aqueous solution 14 put into the pressure vessel 10, the temperature inside the vessel, and the setting of the pressure regulating valve 36. Therefore, the amount of the aqueous solution 14 put into the pressure vessel 10 may be adjusted so that the pressure inside the vessel is 22.1 MPa or higher when the temperature inside the vessel is 390° C. or higher. This state is maintained for a predetermined time, and then the internal temperature of the pressure vessel 10 is cooled to room temperature, after which the base substrate 52 (composite substrate 50) with the α-Ga2O3 crystal film 54 attached thereto is taken out of the pressure vessel 10, rinsed with pure water, and then dried in a dryer.

[0025] [Manufacturing method of gallium oxide crystal film] Next, a method for producing a gallium oxide crystal film will be described. One example of a method for producing a gallium oxide crystal film is to remove the base substrate 52 from the composite substrate 50 to obtain a free-standing α-Ga2O3 crystal film 54. Methods for removing the base substrate 52 from the composite substrate 50 include grinding, polishing, laser lift-off, etching the substrate portion with acid or alkali, and RIE (reactive ion etching). By removing the base substrate 52 from the composite substrate 50, a free-standing α-Ga2O3 crystal film 54 can be obtained. The α-Ga2O3 crystal film 54 may be transferred onto another substrate as long as the base substrate 52 has been removed.

[0026] The composite substrate 50 and the manufacturing method of the composite substrate 50 described above can provide a composite substrate in which peeling between the α-Ga2O3 crystal film 54 and the base substrate 52 is suppressed. The reason for obtaining such an effect is presumably, for example, that the α-Ga2O3 crystal film 54 contains at least one type of alkali metal element at a suitable concentration. In addition, since the α-Ga2O3 crystal film 54 contains at least one type of alkali metal element at a suitable concentration, it is expected that heterophases such as β-Ga2O3 are suppressed and α-Ga2O3 crystals are stably generated. The manufacturing method of the composite substrate 50 is suitable for manufacturing the composite substrate 50. In the manufacturing method of the gallium oxide crystal film, the base substrate 52 is removed from the composite substrate 50 in which peeling between the α-Ga2O3 crystal film 54 and the base substrate 52 is suppressed and there are few cracks, so that the α-Ga2O3 crystal film 54 is obtained as a free-standing film. In the composite substrate 50, the ratio of the peeled area between the α-Ga2O3 crystal film 54 and the base substrate 52 may be, for example, 10% or less of the formation surface 52a, and preferably 3% or less.

[0027] In addition, in the composite substrate 50, the thickness of the α-Ga2O3 crystal film 54 is 10 μm or more, so that by removing the base substrate 52, a self-supporting α-Ga2O3 crystal film 54 having a thickness of 10 μm or more can be obtained. Such an α-Ga2O3 crystal film 54 is suitable for use in a vertical-structure power semiconductor that requires current to flow in the thickness direction. The thickness of the α-Ga2O3 crystal film 54 may be adjusted appropriately depending on the application, and may be, for example, 100 μm or less. The thickness of the α-Ga2O3 crystal film 54 can be adjusted, for example, by changing the amount or concentration of Ga used and the time of hydrothermal synthesis.

[0028] Furthermore, in the composite substrate 50, the base substrate 52 is an α-Cr2O3 substrate, and therefore the α-Ga2O3 crystal film is grown under favorable conditions, thereby further suppressing delamination between the α-Ga2O3 crystal film 54 and the base substrate 52.

[0029] Furthermore, in the composite substrate 50, it is preferable that the crystal orientation difference between the (0001) plane and the (10-10) plane of the α-Ga2O3 crystal film 54 and the base substrate 52 is 0.4° or less, in other words, the crystal orientation is almost the same as that of the base substrate 52. If the crystal orientation is almost the same, distortion is unlikely to occur between the α-Ga2O3 crystal film 54 and the base substrate 52, and peeling between them is further suppressed. The crystal orientation difference between the (0001) plane and the (10-10) plane is more preferably 0.3° or less, more preferably 0.2° or less, and even more preferably 0.1° or less.

[0030] Furthermore, when the α-Ga2O3 crystal is used in a power semiconductor or the like that requires high withstand voltage, the dielectric breakdown field characteristic is affected by the crystal quality, and therefore high crystal quality is required. Therefore, in the composite substrate 50, the α-Ga2O3 crystal film 54 preferably has an X-ray rocking curve half width of 2000 arcsec or less for both the (006) plane and the (104) plane, in other words, has sufficiently high crystallinity (crystal quality). The X-ray rocking curve half width of the (006) plane is preferably 1600 arcsec or less, may be 1000 arcsec or less, or may be 100 arcsec or less. The X-ray rocking curve half width of the (104) plane is preferably 1900 arcsec or less, may be 1000 arcsec or less, or may be 400 arcsec or less. The X-ray rocking curve half width of the (006) plane and the (104) plane may each be 50 arcsec or more.

[0031] In the composite substrate 50, the α-Ga2O3 crystal film 54 has a Cr and / or Ni content of 2.0×10 15 ~1.0×10 17 atoms / cm 3 In this way, peeling between the α-Ga2O3 crystal film 54 and the base substrate 52 is further suppressed. In addition, when the content of each of Cr and Ni is 2.0×10 15 ~1.0×10 17 atoms / cm 3 In addition, the total content of Cr and Ni is preferably 1.6×10 17 atoms / cm 3 It is preferable that the value is less than 5.0×10 16 atoms / cm 3 It is more preferable that:

[0032] Furthermore, in the composite substrate 50, the α-Ga2O3 crystal film 54 has a Li, Na and K content of 1.2×10 15 ~1.0×10 18 atoms / cm 3In addition, the total content of each of Li, Na and K is preferably 1.2×10 15 ~1.2×10 18 atoms / cm 3 It is preferable that:

[0033] It goes without saying that the present invention is not limited to the above-described embodiment, and can be embodied in various forms within the technical scope of the present invention.

[0034] For example, in the above embodiment, the base substrate 52 is an α-Cr2O3 substrate, but the base substrate 52 may be a sapphire substrate, an α-Fe2O3 substrate, an α-Ga2O3 substrate, or the like. However, depending on the type of base substrate 52, the α-Ga2O3 crystal may be generated in a particulate form rather than a film form, or a different phase such as a β-Ga2O3 crystal may be generated. If the base substrate 52 is an α-Cr2O3 substrate, the α-Ga2O3 crystal is easily generated in a film form and a different phase is unlikely to be generated, so this is preferable. In particular, if the base substrate 52 is an α-Cr2O3 solid solution substrate, the crystallinity of the α-Ga2O3 crystal film 54 is higher and the crystal orientation difference between the α-Ga2O3 crystal film 54 and the base substrate 52 is smaller, so this is preferable. EXAMPLES

[0035] EXAMPLES The present invention will be described below with reference to examples, but the present invention is not limited to the following examples in any way.

[0036] [Example 1] 1. Preparation of the substrate A commercially available c-plane (no off-angle) α-Cr2O3 single crystal substrate, which is a high-purity α-Cr2O3 substrate, was cut into a 4 mm square (□4 mm), and both sides were mirror-polished with diamond slurry, after which one side was further finished by CMP treatment. The surface finished by CMP treatment is also called the base CMP surface, and the other surface is also called the base non-CMP surface.

[0037] 2. Hydrothermal synthesis A 0.1 M aqueous solution of gallium nitrate octahydrate (Kishida Chemical) was prepared, and the pH was adjusted to 10.0 using a 1 M aqueous solution of KOH as a pH adjuster to obtain a raw material solution. Next, a 4 mm square c-plane α-Cr2O3 single crystal substrate (base substrate 52) was placed on a 50 μm thick Pt foil with a height of 10 mm, width of 10 mm, and depth of 10 mm in a pressure-resistant container 10 (inner diameter 19 mm, internal volume 50 mL) made of SUS316 as shown in FIG. mm The pressure vessel 10 was placed in the jig 16 with the base CMP surface facing up, and 45 mL of the raw material solution was added and sealed. The pressure vessel 10 was then set in the electric furnace housing 22 of the hydrothermal synthesis system 20. The pressure regulating valve 36 was set in advance so that the internal pressure of the pressure vessel 10 was 30.0 MPa. Next, the entire pressure vessel 10 was heated by the heater 24 of the electric furnace housing 22, and the internal temperature of the pressure vessel 10 was 410°C. At this time, the internal pressure of the pressure vessel 10 was 30.0 MPa. This state was maintained for 24 hours. After the internal temperature of the pressure vessel 10 was cooled to room temperature, the obtained substrate (composite substrate) was taken out of the pressure vessel 10, rinsed with pure water, and then dried in a dryer. In this composite substrate, a crystal film was formed on the base CMP surface.

[0038] 3. Removal of the base substrate The base side surface (base non-CMP surface) of the composite substrate obtained in 2 above was attached to a polishing plate with wax, the surface of the crystal film was polished with diamond slurry, and smoothed by CMP (crystal film CMP surface). The composite substrate was removed from the polishing plate, and a sapphire substrate was bonded to the crystal film CMP surface of the composite substrate with wax to obtain a bonded body. Furthermore, the sapphire surface of the bonded body was attached to a polishing plate with wax, and the base substrate (Cr2O3 portion) was ground and removed using a grinder with #1000 and #6000 grinding stones. This resulted in a gallium oxide crystal film transferred to the sapphire substrate. The sapphire substrate was attached to the gallium oxide crystal film with wax, so it could be easily removed. This resulted in a free-standing gallium oxide crystal film.

[0039] 4. Evaluation (1) Crystal phase An XRD profile was obtained under the following conditions using an XRD device (Rigaku, RINT-TTR III) for the crystals formed on the CMP surface in step 2 above. As a result, the main phase of the formed crystal film was identified as α-Ga2O3. X-ray tube Cu target Tube voltage: 50kV ·Tube current 300mA 2θ / θ method 2θ range: 10°~80°

[0040] (2) Presence or absence of peeling The composite substrate obtained in step 2 above was visually inspected for the presence or absence of delamination between the base substrate and the α-Ga2O3 crystal film. Although slight delamination (less than 3%) was found on the outer periphery of the composite substrate, no overall delamination was observed.

[0041] (3) Microstructure observation The surface of the composite substrate (α-Ga2O3 crystal film surface) obtained in 2 above was observed with a scanning electron microscope (SEM, JEOL JSM-IT500), and the crystal film shown in Figure 4 was confirmed. After embedding the substrate in resin, a cross section was made with a microcutter, and a specimen for cross-sectional observation was prepared with a cross-section polisher (JEOL IB-19500CP). The backscattered electron image of the obtained cross section was taken with a scanning electron microscope (Hitachi High-Technologies SU-5000). At this time, as shown in Figure 5, the α-Cr2O3 (base substrate) and the α-Ga2O3 crystal film of the composite substrate can be easily distinguished from each other by the contrast difference. The thickness of the α-Ga2O3 crystal film was measured from this cross-sectional SEM image. The results are shown in Table 1. As can be seen from Figures 4 and 5, almost no fine holes were confirmed in the crystal film formed on the base substrate.

[0042] (4) X-ray rocking curve half-width Using an XRD device (D8-DISCOVER, manufactured by Bruker-AXS), XRC measurements were performed on the (006) and (104) planes of the crystals formed on the CMP surface in the above step 2. Specifically, 2θ, ω, χ, and φ were adjusted to set the axis so that the peak of the (006) or (104) plane of α-Ga2O3 appeared, and then the conditions were as follows: tube voltage 40 kV, tube current 40 mA, anti-scattering slit 3 mm, ω = 20.0 to 20.4° range for (006) plane measurement, ω = 16.5 to 17.5° range for (104) plane measurement, ω step width 0.001°, and counting time 0.5 seconds. In addition, the X-ray source used was a Ge (022) asymmetric reflection monochromator that converted CuKα rays into parallel monochromatic light. The half-width of the obtained XRC profile of α-Ga2O3 was determined by smoothing the profile and then searching for a peak using XRD analysis software (Bruker-AXS, "LEPTOS" Ver. 4.03). The results are shown in Table 1.

[0043] (5) EBSD (Electron Backscatter Diffraction) Using the sample prepared for cross-sectional observation in (3) above, EBSD measurement was carried out using a scanning electron microscope (SU-5000, manufactured by Hitachi High-Technologies Corporation) combined with EBSD (Nordlys Nano, manufactured by Oxford Instruments Japan K.K.). From the obtained inverse pole figure orientation mapping, it was found that the α-Ga2O3 crystal film is an orientation layer with c-axis orientation in the substrate normal direction and is also a biaxially oriented layer oriented in the in-plane direction of the substrate. Furthermore, in the obtained crystal orientation mapping, the tilt angle distributions of α-Ga2O3 and α-Cr2O3 with respect to the (0001) orientation and the (10-10) orientation were analyzed, and the difference in the peak top positions of the obtained angle distributions was calculated. Specifically, first, for the crystal orientation mapping image measured in a field of view including both the α-Ga2O3 film and the α-Cr2O3 substrate, in the histogram of the tilt angle distribution displayed by Legend in the analysis program, with the class width of the histogram set to 0.010, the peak top position of the tilt angle distribution of the α-Ga2O3 film portion in the (0001) orientation was within the range of 10 to 11 degrees, and the peak top position of the tilt angle distribution of the α-Ga2O3 film portion in the (10-10) orientation was within the range of 10 to 11 degrees. Alignment was performed using the virtual Chamber of the analysis program. At this time, the angle of the peak top position of the tilt angle distribution of the α-Ga2O3 film portion in the (0001) orientation was set as c1 [°] (10 < c1 < 11), and the angle of the peak top position of the tilt angle distribution of the α-Ga2O3 film portion in the (10-10) orientation was set as a1 [°] (10 < a1 < 11). Subsequently, while maintaining the aligned state, the angle c2 [°] of the peak top position of the tilt angle distribution of the (0001) orientation of the underlying substrate (α-Cr2O3) portion was obtained, and the (0001) orientation difference between the underlying substrate and the α-Ga2O3 film was calculated as |c1 - c2| [°]. Similarly, the angle a2 [°] of the peak top position of the tilt angle distribution of the (10-10) orientation of the underlying substrate (α-Cr2O3) portion was obtained, and the (10-10) orientation difference between the underlying substrate and the α-Ga2O3 film was calculated as |a1 - a2| [°]. The results are shown in Table 1.From these results, in Example 1, the orientation difference between the underlying substrate and the α-Ga2O3 film was 0.10 degrees in the (0001) orientation and 0.13 degrees in the (10-10) orientation. It was found that an α-Ga2O3 film with almost the same crystal orientation as the underlying substrate was obtained. In the above description, the crystal orientation

[0001] of the (0001) plane was described as the (0001) orientation, and the crystal orientation [10-10] of the (10-10) plane was described as the (10-10) orientation. The various conditions for EBSD measurement were as follows. <EBSD Measurement Conditions> ·Acceleration voltage: 15 kV ·Spot intensity: 70 ·Working distance: 22.5 mm ·Step size: 0.4 μm ·Sample tilt angle: 70° ·Measurement program: AZtec ·Analysis program: OXFORD HKL CHANNEL5

[0044] (6) Composition analysis Using a secondary ion mass spectrometer (SIMS), composition analysis (D-SIMS analysis) of the α-Ga2O3 crystal film on the surface of the composite substrate obtained in (2) above was performed. The various conditions for this D-SIMS analysis were as follows. <D-SIMS Analysis Conditions> ·Equipment: IMS-7f manufactured by CAMECA ·Primary ion species: O2 + ·Primary ion acceleration voltage: 8.0 kV The content of each ion was converted to the unit of "atoms / cm 3 " using a Ga2O3 standard sample, a depth profile was created, and the average value of the values at a depth of 1 μm to 2 μm from the surface was obtained. The results are shown in Table 1.

[0045] [Example 2] In preparing the raw material solution, a 1M LiOH solution was used as a pH adjuster, the pH of a 0.1M aqueous solution of gallium nitrate octahydrate was adjusted to 10.5, and the internal temperature of the pressure vessel 10 was set to 400°C. Except for this, the samples were prepared and evaluated in the same manner as in Example 1. The main phase of the crystal film formed on the base substrate was α-Ga2O3. The various evaluation results are shown in Table 1.

[0046] [Example 3] In preparing the raw material solution, a 1M NaOH solution was used as a pH adjuster, and the pH of the 0.1M aqueous solution of gallium nitrate octahydrate was adjusted to 9.5. Except for this, the samples were prepared and evaluated in the same manner as in Example 1. The main phase of the crystal film formed on the base substrate was α-Ga2O3. The various evaluation results are shown in Table 1.

[0047] [Example 4] A base substrate, which is an α-Cr2O3 solid solution substrate, was prepared as follows. 100 parts by weight of Cr2O3 powder was added with 5 parts by weight of TiO2 powder and 16 parts by weight of Fe2O3 powder as raw material powder, and the mixed powder was wet mixed to form an AD film on a sapphire substrate (diameter 50.8 mm (2 inches), thickness 1.0 mm, c-plane, off-angle 0.5°) by an AD (aerosol deposition) apparatus 120 shown in FIG. 6. The AD apparatus 120 shown in FIG. 6 is configured as an apparatus used in the AD method in which raw material powder is sprayed onto a substrate under an atmosphere of lower pressure than atmospheric pressure. This film forming apparatus 120 includes an aerosol generating section 122 that generates an aerosol of raw material powder containing raw material components, and a film forming section 130 that sprays the raw material powder onto a sapphire substrate 121 to form a film containing the raw material components. The aerosol generating section 122 includes an aerosol generating chamber 123 that receives a carrier gas from a gas cylinder (not shown) and stores raw material powder to generate an aerosol, a raw material supply pipe 124 that supplies the generated aerosol to the film forming section 130, and a vibrator 125 that applies vibrations at a frequency of 10 to 100 Hz to the aerosol generating chamber 123 and the aerosol therein. The film forming section 130 includes a film forming chamber 132 that sprays the aerosol onto the sapphire substrate 121, a substrate holder 134 that is disposed inside the film forming chamber 132 and fixes the sapphire substrate 121, and an XY stage 133 that moves the substrate holder 134 in the X-axis and Y-axis directions. The film forming section 130 also includes an injection nozzle 136 that has a slit 137 formed at its tip and sprays the aerosol onto the sapphire substrate 121, and a vacuum pump 138 that reduces the pressure in the film forming chamber 132.

[0048] The AD film formation conditions were as follows. That is, the carrier gas was Ar, and a ceramic nozzle with a slit of 5 mm long side × 0.3 mm short side was used. The nozzle scan conditions were a scan speed of 0.5 mm / s, and the nozzle was moved 55 mm in a direction perpendicular to the long side of the slit and forward, 5 mm in a direction perpendicular to the long side of the slit and back, and 5 mm in a direction opposite to the initial position of the long side of the slit. When the nozzle was moved 55 mm from the initial position in the direction of the long side of the slit, the nozzle was scanned in the opposite direction to the direction up to that point, and the cycle of returning to the initial position was counted as one cycle, and this cycle was repeated 400 times. In one cycle of film formation at room temperature, the set pressure of the carrier gas was adjusted to 0.07 MPa, the flow rate to 9 L / min, and the chamber pressure to 100 Pa or less. The AD film formed in this way had a thickness of about 100 μm.

[0049] The sapphire substrate on which the AD film was formed was removed from the AD device and annealed at 1680°C for 4 hours in a nitrogen atmosphere. The substrate thus obtained was fixed to a ceramic surface plate, and the surface on which the AD film was formed was ground to #2000 using a grindstone to make the surface flat. The surface was then smoothed by lapping using diamond abrasive grains. The size of the abrasive grains was gradually reduced from 3μm to 0.5μm to improve flatness. After cutting into a size of □4mm using a dicer, a mirror finish was performed by chemical mechanical polishing (CMP) using colloidal silica to obtain a composite base substrate. The arithmetic mean roughness Ra after processing was 0.1nm, the amount of grinding and polishing was 50μm, and the thickness of the composite base substrate after polishing was 1.05mm. The surface on which the AD film was formed is referred to as the "front surface".

[0050] Composition analysis of the composite substrate surface was performed using an electron probe microanalyzer (FE-EPMA) (JEOL Ltd., electron probe microanalyzer, JXA-8500F) with a probe size of 30 μm × 30 μm. FE-EPMA measurements were performed under measurement conditions of an acceleration voltage of 15 kV and an irradiation current of 50 nA. As a result, Cr, O, Ti, and Fe were detected. The quantitative values ​​of the detected elements (atomic composition percentages of atoms excluding O) were 83.7 at% for Cr, 3.7 at% for Ti, and 12.6 at% for Fe.

[0051] A sample was prepared and evaluated in the same manner as in Example 1, except that the composite base substrate prepared as described above was used with the AD film (α-Cr2O3 solid solution substrate) side facing up. The main phase of the crystal film formed on the base substrate was α-Ga2O3. Various evaluation results are shown in Table 1.

[0052] [Table 1]

[0053] [Comparative Example 1] A 4 mm square c-plane sapphire substrate (without off-angle, surface CMP-treated) was used as the base substrate, and an α-Ga2O3 crystal film was fabricated by the mist CVD method as follows. The raw material solution was an aqueous solution containing 1.5% by volume of 36% hydrochloric acid with a gallium acetylacetonate concentration of 0.08 mol / L. This raw material solution was made into mist by vibrating it at 2.4 MHz using an ultrasonic vibrator, and introduced into the film-forming chamber by nitrogen gas. In the film-forming chamber, the substrate was placed on a susceptor installed inside, and the chamber was heated to 490°C in advance. The mist-formed raw material solution was layered in a film form by the CVD reaction on the surface of the base substrate, so this film formation was performed for 60 minutes, and by repeating this five times, a crystal film was layered on the base substrate. The main phase of the crystal film formed on the base substrate was confirmed to be α-Ga2O3 by XRD. In Comparative Example 1, more than 50% of the film was peeled off by visual inspection, and many cracks were observed around the peeled parts, so the film thickness was measured by observing the cross section of a part where peeling had not occurred. The various evaluation results are shown in Table 2.

[0054] [Comparative Example 2] An α-Cr2O3 substrate similar to that in Example 1 was used as the base substrate, and an α-Ga2O3 crystal film was produced by the mist CVD method in the same manner as in Comparative Example 1. However, 60-minute film formation was repeated 10 times for a total of 600 minutes. The main phase of the crystal film formed on the base substrate was confirmed to be α-Ga2O3 by XRD. In Comparative Example 2, more than 40% of the film was peeled off by visual inspection, and many cracks were generated around the peeled parts. The film thickness was measured by observing the cross section of a part where peeling had not occurred. Various evaluation results are shown in Table 2.

[0055] [Table 2]

[0056] As shown in Table 2, the content of each alkali metal element in the α-Ga2O3 crystal film is 1.2×10 15 atoms / cm 3 In Comparative Examples 1 and 2, where the content of at least one alkali metal element was less than 1.2 × 10, peeling occurred over a wide area between the α-Ga2O3 crystal film and the base substrate. 15 ~1.0×10 18 atoms / cm 3 In Examples 1 to 4, the peeling between the α-Ga2O3 crystal film and the base substrate was suppressed, and the peeled area was 3% or less in all cases. In addition, in Examples 1 to 4, the crystal orientation difference between the (0001) plane and the (10-10) plane of the α-Ga2O3 crystal film and the base substrate was 0.4° or less in all cases, and the half-width of the X-ray rocking curve of the (006) plane and the (104) plane of the α-Ga2O3 crystal film was 2000 arcsec or less in all cases.

[0057] In this specification, the use of "to" indicating a range of values ​​means that the values ​​before and after it are included as the lower limit and upper limit.

[0058] This application claims priority from Japanese Patent Application No. 2021-075004, filed on April 27, 2021, the entire contents of which are incorporated herein by reference. [Industrial Applicability]

[0059] The present invention can be used, for example, as materials for power semiconductors. [Explanation of symbols]

[0060] 10 pressure vessel, 11 vessel body, 12 lid, 12a protrusion, 14 aqueous solution containing Ga ions, 16 jig, 20 hydrothermal synthesis system, 22 electric furnace housing, 24 heater, 26 thermocouple for measuring temperature inside the furnace, 28 thermocouple for pressure vessel, 30 piping, 30a one end, 30b other end, 32 pressure gauge, 34 safety valve, 36 pressure adjustment valve, 40 cooling water tank, 50 composite substrate, 52 base substrate, 52a formation surface, 54 α-Ga2O3 crystal film, 55 α-Ga2O3 crystal, 120 AD device, 121 sapphire substrate, 122 aerosol generation unit, 123 aerosol generation chamber, 124 raw material supply pipe, 125 vibrator, 130 film formation unit, 132 film formation chamber, 133 XY stage, 134 Substrate holder, 136 injection nozzle, 137 slit, 138 vacuum pump.

Claims

1. A base substrate; A film having a thickness of 10 μm or more and a content of at least one alkali metal element of 1.2×10 15 atoms / cm 3 Above 1.0 x 10 18 atoms / cm 3 α-Ga 2 O 3 A crystalline film; Equipped with The base substrate is an α-Cr 2 O 3 substrate; Composite board.

2. The α-Ga 2 O 3 the crystal film has a crystal orientation difference between the (0001) plane and the (10-10) plane of the base substrate of 0.4° or less; The composite substrate according to claim 1 .

3. The α-Ga 2 O 3 The crystalline film has an X-ray rocking curve half-width of 2000 arcsec or less for both the (006) plane and the (104) plane. The composite substrate according to claim 1 or 2.

4. The α-Ga 2 O 3 The crystal film has a Cr and / or Ni content of 2.0×10 15 atoms / cm 3 Above 1.0 x 10 17 atoms / cm 3 Below is the The composite substrate according to any one of claims 1 to 3.

5. The α-Ga 2 O 3 The crystalline film has a Li, Na and K content of 1.2×10 15 atoms / cm 3 Above 1.0 x 10 18 atoms / cm 3 Below is the The composite substrate according to any one of claims 1 to 4.

6. A method for producing the composite substrate according to any one of claims 1 to 5, comprising the steps of: The starting substrate is immersed in an aqueous solution containing Ga ions, and the solution is placed in a supercritical state at a temperature of 390° C. or higher and a pressure of 22.1 MPa or higher, whereby the α-Ga ions are formed on the surface of the starting substrate. 2 O 3 Generate a crystalline film, Manufacturing method for composite substrate.

7. The aqueous solution contains an alkali metal element. A method for producing the composite substrate according to claim 6.

8. The α-Ga GaN self-supporting layer is formed by removing the base substrate from the composite substrate according to any one of claims 1 to 5. 2 O 3 Obtaining a crystalline film, A method for producing gallium oxide crystal films.

9. The composite substrate produced by the method of claim 6 or 7 is subjected to removal of the base substrate, and the free-standing α-Ga 2 O 3 Obtaining a crystalline film, A method for producing gallium oxide crystal films.

Citation Information

Patent Citations

  • Method for preparing beta-gallium oxide by microwave hydrothermal method

    CN101993110A

  • Gallium oxide phase junction nanopillar array and preparation method thereof

    CN107841785A

  • High-crystallinity conductive alpha type gallium oxide thin film with dopant added, and method of forming the same

    JP2013028480A

  • Semiconductor device

    JP2014072533A

  • Semiconductor device

    JP2016025256A